PENGARUH EDUKASI SKRINING JIWA TERHADAP PENGETAHUAN KADER KESEHATAN TENTANG DETEKSI DINI GANGGUAN MENTAL IBU HAMIL - Hana Rosiana Ulfah; Muhammad Amin Ghozy; Emy Kurniawati; Farhan Nafis Sajidallah; Resi Putri Naulia (Jurnal Cakrawala Keperawatan, 2026)
Background: The proficiency of community health workers in grasping health- related concepts serves as the bedrock for successful disease prevention and health promotion initiatives. Regrettably, insufficient training programs and limited informational resources often compromise their effectiveness in delivering primary healthcare services. Objective: This quantitative investigation examines the efficacy of health education workshops in enhancing community health volunteers' comprehension of targeted medical subjects. Methods: The study employed a quasi-experimental design featuring pre- and post-intervention assessments within a single test group. Thirty certified community health workers participated in the trial, receiving specialized training through instructional seminars complemented by interactive learning sessions. Participant knowledge levels were quantitatively measured using validated questionnaires before and after the intervention, with subsequent data processing conducted through nonparametric statistical analysis. Results: Participant demographics: Majority (80%) completed secondary education, with homemakers constituting 63% of the cohort. Baseline evaluation: Moderate understanding (70%), limited comprehension (30%), with no participants demonstrating complete mastery. Post-intervention results: Significant knowledge improvement with 80% achieving mastery and 20% showing intermediate understanding. Statistical analysis confirmed intervention effectiveness (p<0.001). Conclusion: The educational initiative demonstrated measurable success in upgrading health volunteers' expertise. Sustainable implementation of similar training programs is recommended to continually enhance service delivery capabilities in community healthcare settings.